A kinematic analysis of jumping technique in elite Korean teeterboard athletes: a case-study - Cossin, M.; Ross, A.; Prince F. (Sports Biomechanics, 2023)
Korean teeterboard is a circus discipline that consists of a board pivoted at its centre upon which two acrobats are catapulted in turn performing acrobatic jumps. This paper presents one of the first studies that focuses on investigating the factors that contribute to jump height in Korean teeterboard. A total of 120 jumps were recorded from two acrobats using motion capture. Selected variables were input to a Boosted Regression Trees (BRT) analysis, corresponding to three specific events: acrobat landing, rotation of the teeterboard and acrobat take-off. Significant predictor variables were identified as: 1) body`s centre of mass vertical velocity at the first contact with the teeterboard (relative importance: 69.4%) for landing, 2) maximum downward vertical teeterboard velocity for teeterboard rotation (72.7%) and 3) maximum upward vertical teeterboard velocity for take-off (50.4%). Kinematic parameters such as hip range of motion during take-off also contributed significantly to jump height (37.2%). The results provide understanding of the complex kinematics between two acrobats and a flexible pivoting board. Teeterboard designers, acrobats and trainers should be aware that maximising these parameters are the best strategies to improve jump height.